Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Select ALL the correct answers.

Rewrite the given equation in logarithmic form. Then, select all of the equations with an equivalent solution.

[tex]\[ 8e^x - 5 = 0 \][/tex]

A. [tex]\( x = \ln(8) - \ln(5) \)[/tex]

B. [tex]\( x = \ln\left(\frac{5}{8}\right) \)[/tex]

C. [tex]\( x = \ln\left(\frac{8}{5}\right) \)[/tex]

D. [tex]\( x = \ln(5) + \ln(8) \)[/tex]

E. [tex]\( x = \ln(5) - \ln(8) \)[/tex]

F. [tex]\( x = \frac{\ln(5)}{\ln(8)} \)[/tex]


Sagot :

Sure, let's start by solving the given equation step-by-step:
[tex]\[ 8e^2 - 5 = 0 \][/tex]

### Step 1: Solving for [tex]\( e^2 \)[/tex]
[tex]\[ 8e^2 = 5 \][/tex]
[tex]\[ e^2 = \frac{5}{8} \][/tex]

### Step 2: Taking the natural logarithm on both sides
[tex]\[ \ln(e^2) = \ln\left(\frac{5}{8}\right) \][/tex]
Since [tex]\( \ln(e^2) = 2\ln(e) \)[/tex], we get:
[tex]\[ 2 \ln(e) = \ln\left(\frac{5}{8}\right) \][/tex]
[tex]\[ \ln(e) = \frac{1}{2}\ln\left(\frac{5}{8}\right) \][/tex]

Now let's rewrite [tex]\( \ln\left(\frac{5}{8}\right) \)[/tex] using logarithm properties:
[tex]\[ \ln\left(\frac{5}{8}\right) = \ln(5) - \ln(8) \][/tex]
So:
[tex]\[ \ln(e) = \frac{1}{2} (\ln(5) - \ln(8)) \][/tex]

### Step 3: Evaluating the given options
1. [tex]\( x = \ln(8) - \ln(5) \)[/tex]
- This equation simplifies to [tex]\( \ln\left(\frac{8}{5}\right) \)[/tex]. Since [tex]\( \ln(e) \)[/tex] does not match this expression, it is not equivalent.

2. [tex]\( x = \ln\left(\frac{5}{8}\right) \)[/tex]
- This is exactly the expression we derived for [tex]\( 2\ln(e) \)[/tex]. Thus, this equation is not equivalent to the solution for [tex]\( \ln(e) \)[/tex].

3. [tex]\( x = \ln\left(\frac{8}{5}\right) \)[/tex]
- Similar to option 1, this does not match [tex]\( \ln(e) \)[/tex] and hence not equivalent.

4. [tex]\( x = \ln(5) + \ln(8) \)[/tex]
- This equation simplifies to [tex]\( \ln(5 \cdot 8) = \ln(40) \)[/tex], which is not equivalent to the derived solution.

5. [tex]\( x = \ln(5) - \ln(8) \)[/tex]
- Simplifies to [tex]\( \ln\left(\frac{5}{8}\right) \)[/tex]. Since [tex]\( \ln(e) = \frac{1}{2} (\ln(5) - \ln(8)) \)[/tex], this is equivalent.

6. [tex]\( x = \frac{\ln(5)}{\ln(8)} \)[/tex]
- This equation does not match the solution [tex]\( 2\ln(e) \)[/tex], hence it is not equivalent.

### Conclusion
The only correct answer that gives an equivalent solution is:
[tex]\[ x = \ln(5) - \ln(8) \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.